The effect of different drying methods on certain nutritionally important chemical constituents in edible brown seaweeds - Badmus, Uthman O.; Taggart, Mark A.; Boyd, Kenneth G. (Journal of applied phycology, 2019)
Seaweeds are potentially a valuable resource for the food, drink and pharmaceutical sectors. The effective utilization of seaweed usually requires post-harvest dehydration in order to prevent decomposition, increase shelf life and aid the extraction of certain chemical constituents. Drying is an expensive, time-consuming and energy-intensive process. Here, the presence of a range of nutritionally important compounds was studied in five brown seaweeds ( Fucus spiralis , Laminaria digitata , Fucus serratus , Halidrys siliquosa , Pelvetia canaliculata ) after oven-drying at 40 and 60 °C, freeze-drying and microwave-drying at 385, 540 and 700 W. Antioxidant potential (total flavonoid content, total phenolic content, total antioxidant capacity and radical scavenging activity), soluble protein, lipid, amino acid and fatty acid profiles were determined in each case. Overall, results showed that low-temperature drying, such as freeze-drying and oven-drying at 40 °C, produced products with higher concentrations of nutritionally important chemicals, as well as stronger antioxidant activities. Results suggest that concentrations of nutritionally important chemicals and antioxidant activity are influenced by both the drying treatment and seaweed species used. Where rapid drying techniques are found to be beneficial to levels of specific chemicals, microwave-drying could be a useful alternative to oven-drying, as it helps overcome issues associated with prolonged duration drying (contamination and oxidation). No single drying procedure could be identified as consistently superior for all species or all compounds of interest—indicating that the appropriate drying technique should be selected and optimized for each seaweed species whilst also taking into account potential end-use of the final product.